المخاطرة السياسية وانعكاساتها على تدفقات الاستثمار الأجنبي المباشر - العامري محمد علي; نعمة نغم حسين (Journal of Economics and Administrative Sciences, 2007)
The searchers opinions are variant in determining the extent of impacting political risk in the host country on foreign direct investment decision. (Aharoni,1966) found, in his questionary study for group of foreign companies operating in India, that a political stability is one of the two most important factors, besides the market size, in the attraction of foreign investment, and its availability means that whether this specific country is good for foreign investment. On the other side, (Green and Benntt, 1972) are present a variant opinion to Aharonis opinion. They are reach to result state that a political instability do not impact on the general distribution of foreign investment, and the foreign investment decision is influenced by the political stability of host country, in determining the required return from this investment, but not in determining the investment size and its place. In other words, the required rate of return on investment in the political instable country is higher than in the political stable country. Thus, when the transnational companies are open its subsidiaries in the foreign countries become exposed to the political risk which is represented by the political activities of the host government, so the latter my be imposing higher tax rates on the subsidiaries as a reaction to its government policies, or my be deciding purchase the subsidiary at any price it determine and think it as fair price, and my be expropriating or nationalizing the parents subsidiaries. So, the political risk management is becoming inevitable matter to the transnational companies and the political risk managers should be taking in their accounts and when they are planning that the request or aspiration level is not just aversing or hedging this risk, but also managing every thing for their good and changing in favorable circumstances to the favorable ones use it in their favor.